2002
DOI: 10.1152/ajpendo.00113.2001
|View full text |Cite
|
Sign up to set email alerts
|

Double isotope tracer method for measuring fractional zinc absorption: theoretical analysis

Abstract: Several approaches for estimation of fractional zinc absorption (FZA) by calculating the ratio of oral to intravenous stable isotopic tracer concentrations (at an appropriate time) in urine or plasma after their simultaneous administration have been proposed in the last decade. These simple-to-implement approaches, often referred to as the double isotopic tracer ratio (DITR) method, are more attractive than the classical “deconvolution” method and the more commonly used single-tracer methods based on fecal mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…We have already had reassurance that results using our dual isotope tracer ratio (DITR) technique based on measurements of isotopic enrichment in urine [1215] for measuring absorption of extrinsic zinc label compare well with results of other techniques, including deconvolution and data obtained from compartmental modeling [22]. The other major question is whether our extrinsic labeling technique provides an accurate measure of the absorption of dietary zinc that has been extrinsically labeled.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have already had reassurance that results using our dual isotope tracer ratio (DITR) technique based on measurements of isotopic enrichment in urine [1215] for measuring absorption of extrinsic zinc label compare well with results of other techniques, including deconvolution and data obtained from compartmental modeling [22]. The other major question is whether our extrinsic labeling technique provides an accurate measure of the absorption of dietary zinc that has been extrinsically labeled.…”
Section: Discussionmentioning
confidence: 98%
“…NAZ was determined from the difference between total dietary zinc and total fecal zinc for the 6-day metabolic period. FAZ extrinsic was determined by a dual isotope tracer ratio technique (DITR) [1215], in which extrinsic zinc stable isotope label was administered with each meal for the same 6-day period. The study timeline is summarized in Figure l.…”
Section: Methodsmentioning
confidence: 99%
“…It is recommended as the method of choice for determination of fractional zinc absorption (12, 13, 15, 19). The technique applied to a spot urine specimen is easy to implement and not sensitive to participant compliance.…”
Section: Discussionmentioning
confidence: 99%
“…We collected only a single spot urine collection at 2 d after isotope dosing to assess Zn absorption, which we believe is adequate for this purpose. Sparacino et al ( 39 ) have shown that this is mathematically equivalent to measuring the isotopes in a single serum sample. As such, it slightly underestimated true Zn absorption.…”
Section: Discussionmentioning
confidence: 99%